Molecular Signaling and Nutritional Regulation in the Context of Poultry Feather Growth and Regeneration - Chen, Meng-jie; Xie, Wen-yan; Jiang, Shi-guang; Wang, Xiu-qi; Yan, Hui-chao; Gao, Chun-qi (Frontiers in Physiology, 2020)
The normal growth and regeneration of feathers is important for improving the welfare and economic value of poultry. Feather follicle stem cells are the basis for driving feather development and are regulated by various molecular signaling pathways in the feather follicle microenvironment. To date, the roles of the Wnt, Bone Morphogenetic Protein (BMP), Notch, and Sonic Hedgehog (SHH) signaling pathways in the regulation of feather growth and regeneration are among the best understood. While these pathways regulate feather morphogenesis in different stages, their dysregulation results in a low feather growth rate, poor quality of plumage, and depilation. Additionally, exogenous nutrient intervention can affect the feather follicle cycle, promote the formation of the feather shaft and feather branches, preventing plumage abnormalities. This review focuses on our understanding of the signaling pathways involved in the transcriptional control of feather morphogenesis and explores the impact of nutritional factors on feather growth and regeneration in poultry. This work may help to develop novel mechanisms by which follicle stem cells can be manipulated to produce superior plumage that enhances poultry carcass quality.